Starość w listach św. Hieronima - Ożóg, Monika (Vox Patrum, 2011)
In late antiquity, the Christian thinkers were not too much interested in the old age from the theoretical point of view. What made the old age for the classical thinkers a fault was – for the Christians – a life purpose since it highlighted the primacy of spirit. Jerome – an excellent expert on classic literature – many times touches upon the issue of the old age in his writings; however, he writes about it in the Christian vein, not in the light of the classical criteria.